Citizens’ Perceptions of Public Administration Ethics, Public Service Quality and Politicization of Public Organizations: A Study in Diyarbakır - Müslüm Kayacı (Siyasal: Journal of Political Sciences)
Citizens’ satisfaction with public sector has been a focus of interest especially in new public management literature for almost four decades. For this reason, investigating perceptions and evaluations of citizens for public service quality has become more vital for both scholars and practitioners. Field studies in different contexts can provide evidence for new public management scholars to expand theory and for governments to improve current policies and operations in the bureaucracy. Based on these arguments, this study aims to reveal how politicization in public organizations is harmful for ethics in public administration and public service quality and the importance of ethical public administration to increase the quality of public services. Results from a field survey study in Diyarbakır has provided support for the proposed arguments of the study. Citizens’ perceptions about the increased politicization in public organizations have shown negative relationships with ethical public administration and public service quality. Also, support is found for the positive relationship with ethical public administration and public service quality. Theoretical contributions and practical implications of these findings are also discussed with the limitations of field study in the last section.